2013
DOI: 10.3390/antib2010019
|View full text |Cite
|
Sign up to set email alerts
|

Improving the Therapeutic Potential of Human Granzyme B for Targeted Cancer Therapy

Abstract: Conventional cancer treatments lack specificity and often cause severe side effects. Targeted therapeutic approaches are therefore preferred, including the use of immunotoxins (ITs) that comprise cell-binding and cell death-inducing components to allow the direct and specific delivery of pro-apoptotic agents into malignant cells. The first generation of ITs consisted of toxins derived from bacteria or plants, making them immunogenic in humans. The recent development of human cytolytic fusion proteins (hCFP) co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 182 publications
0
16
0
Order By: Relevance
“…The fusion protein was effectively cleaved at the furin cleavage site within the endosome, translocated to cytosol to provoke cell death, and reduced tumor size in nude mice [17]. An optimal linker can provide many advantages for improved bioactivity and specificity of the fusion protein, potentially facilitating its activity by avoiding steric hindrance or conformational changes [13]. The furinsensitive polyarginine linker we used to connect p28 to GrB, enabled in vivo activation of the fusion protein in tumor cells, which may lead to reduced off-target binding and systemic toxicity of the drug protein [30].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The fusion protein was effectively cleaved at the furin cleavage site within the endosome, translocated to cytosol to provoke cell death, and reduced tumor size in nude mice [17]. An optimal linker can provide many advantages for improved bioactivity and specificity of the fusion protein, potentially facilitating its activity by avoiding steric hindrance or conformational changes [13]. The furinsensitive polyarginine linker we used to connect p28 to GrB, enabled in vivo activation of the fusion protein in tumor cells, which may lead to reduced off-target binding and systemic toxicity of the drug protein [30].…”
Section: Resultsmentioning
confidence: 99%
“…The effector component of a CFP may include an RNase, kinase, protease or another chemotherapeutic agent. Granzyme B (GrB), a 32-KD human serine protease involved in the granule-mediated apoptosis of virus-infected or transformed tumor cells by effector cells of the innate and adaptive immune system, has several inherent advantages as an immunotoxin, including high cytotoxic efficacy, a broad portfolio of apoptosis inducing mechanisms and low immunogenicity [13]. Yet, natural inhibition by serpin B9, a high isoelectric point resulting in a positive surface charge contributing to non-specific binding to normal cells, and relatively slow release after uptake by the receptor-mediated endocytosis have limited the clinical application of GrB [14].…”
Section: Introductionmentioning
confidence: 99%
“…We recently summarized examples of tumor cells, which have been found to express PI-9 to evade granule-mediated killing and might, therefore, be difficult to treat with granzyme B-based immunotherapeutics [73]. Indeed, several studies have confirmed the direct correlation between PI-9 expression and the loss of granzyme B pro-apoptotic activity and cytotoxic lymphocyte activity in vitro and in vivo.…”
Section: Therapeutic Potential and Limitations Of Granzyme B For The mentioning
confidence: 90%
“…It is one of the most important effector molecules for the immune surveillance of virus-infected and transformed tumor cells [99] and is exceptional among the apoptosis-inducing enzymes used in immunotherapeutic approaches because it can induce apoptosis at multiple levels using different pathways [96,97,99]. Granzyme B is therefore more likely to overcome anti-apoptosis mechanisms that evolve in tumor cells and this makes it a potent and reliable inducer of apoptosis in hCFPs [100]. The potential of granzyme B in cancer therapy has been demonstrated by coupling it to antibodies and ligands that target CD64, gp240, ErbB2/Her2 (human epidermal growth factor receptor 2), hLHR (human luteinizing hormone receptor), LeY (Lewis Y antigen), EGFR (epidermal growth factor receptor), and CD30 [100][101][102].…”
Section: "Humanization" Of Immunotoxins Using Granzyme B and Angiogeninmentioning
confidence: 99%
“…Granzyme B is therefore more likely to overcome anti-apoptosis mechanisms that evolve in tumor cells and this makes it a potent and reliable inducer of apoptosis in hCFPs [100]. The potential of granzyme B in cancer therapy has been demonstrated by coupling it to antibodies and ligands that target CD64, gp240, ErbB2/Her2 (human epidermal growth factor receptor 2), hLHR (human luteinizing hormone receptor), LeY (Lewis Y antigen), EGFR (epidermal growth factor receptor), and CD30 [100][101][102]. Granzyme B-based hCFPs have been proven successful in ex vivo experiments [93] and in a xenograft mouse model [102].…”
Section: "Humanization" Of Immunotoxins Using Granzyme B and Angiogeninmentioning
confidence: 99%